Involvement of PI3K/Akt, ERK and p38 signaling pathways in emodin-mediated extrinsic and intrinsic human hepatoblastoma cell apoptosis. (June 2016) - Cui, Yuting; Lu, Peiran; Song, Ge; Liu, Qian; Zhu, Di; Liu, Xuebo
Abstract: As a natural anthraquinone derivative, 1, 3, 8-trihydroxy-6-methylanthraquinone, known as emodin, has recently been reported to possess potential chemopreventive capacity, but the underlying molecular mechanism of its hepatocyte toxicity remains poorly clarified. The present research indicated that emodin targeted HepG2 cells without being cytotoxic to primary human hepatocyte cells in comparison with chrysophanol and rhein. The anti-proliferative effect of emodin was ascribed to occurrence of apoptosis, which characterized by higher ethidium bromide signal, brighter DAPI fluorescence, cleavages of procaspase-3 and poly (ADP-ribose) polymerase as well as quantitative result from Annexin V-FITC/PI double staining. Furthermore, emodin improved Bax/Bcl-2 ratio, elicited disruption of mitochondrial membrane potential and promoted efflux of cytochrome c to cytosol, indicative of features of mitochondria-dependent apoptotic signals. Emodin concurrently led to activations of Fas, Fas-L, caspase-8 and tBid, which provoked death receptor apoptotic signals. Notably, activated tBid relayed the Fas apoptotic signal to the mitochondrial pathway. Besides, emodin effectively attenuated phosphorylations of Akt and ERK and promoted phosphorylation of p38. Inhibitions of PI3K/Akt and ERK and activation of p38 mediated emodin-induced apoptosis through modulating the mitochondrial pathway and/or death receptor pathway. Additionally, there was a cross-talk between PI3K/Akt and MAPKs pathways in emodin-induced apoptosis. Highlights: Emodin exerts more effective anti-proliferative effect on HepG2 cells and less cytotoxicity to primary hepatocyte cells. The extrinsic and intrinsic pathways mediate emodin-induced HepG2 cell apoptosis in which tBid is the molecular linker. Inhibitions of Akt and ERK and activation of p38 mediate emodin-induced apoptosis through regulating downstream pathways. There is a cross-talk between PI3K/Akt and MAPKs signaling pathways in emodin-induced apoptosis.